Creating topsoils and soil conditioners from biosolids and urban residuals. Issue 4 (23rd April 2020) - Batjiaka, Ryan; Brown, Sally
Abstract: A study was conducted to test the suitability of a range of organic and inorganic residuals mixed with municipal biosolids to create a soil amendment effective for a broad range of end uses. Biosolids suitable for unrestricted use were sourced from San Francisco, CA. Residuals including urban wood and yard waste, nut shells, biochar, and sawdust were sourced from nearby producers. Existing biosolids based soil products, peat, and a yard–food compost were used as controls. Experimental mixtures were tested for a range of soil properties, appearance, odor, germination, and growth response. Several mixtures performed as well as or better than the yard–food compost, and several performed comparably to the biosolids soil controls. Yard waste fines blended with biosolids in a 50:50 ratio by volume or yard waste fines blended with biosolids and 20% sand at 40:40:20 were highly effective across all measured indices. Mixed yard and recycled lumber fines blended with biosolids at these same ratios performed similarly well. Blends with a high percentage of char performed poorly in germination and growth response, likely as a result of elevated electrical conductivity. Certain blends such as gypsum and redwood shavings failed to mix well with biosolids to create a uniform looking material and were less visually appealing. In general, blends that met established quality control parameters for compost performed well on the measured indices. These results suggest that blending Class A biosolids with organic and inorganic feedstocks to meet quality criteria developed for compost will create marketable soil products.